2019
DOI: 10.1101/561159
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Programmable bacteria induce durable tumor regression and systemic antitumor immunity

Abstract: Co-corresponding authors SUMMARY PARAGRAPHSynthetic biology is driving a new era of medicine through the genetic programming of living cells 1,2 . This transformative approach allows for the creation of engineered systems that intelligently sense and respond to diverse environments, ultimately adding specificity and efficacy that extends beyond the capabilities of molecular-based therapeutics 3-5 . One particular focus area has been the engineering of bacteria as therapeutic delivery systems to selectively rel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 29 publications
2
54
0
1
Order By: Relevance
“…Myriad strategies employing nanoparticles and even live bacteria as drug delivery vehicles have been proposed for the specific killing of cancerous cells [49][50][51][52] . We suggest that SSHELs provide several unique benefits and that they may be used as an additional strategy for this purpose and may be modified easily to suit different needs.…”
Section: Discussionmentioning
confidence: 99%
“…Myriad strategies employing nanoparticles and even live bacteria as drug delivery vehicles have been proposed for the specific killing of cancerous cells [49][50][51][52] . We suggest that SSHELs provide several unique benefits and that they may be used as an additional strategy for this purpose and may be modified easily to suit different needs.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups are taking the approach to BCT to engineer the bacteria to deliver drugs or other compounds that can further promote tumor death or immune clearance (19,20,(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Effective treatment with STm has been observed in adaptive immune-deficient (nude) mouse models (8,18), suggesting that T cell responses may not be essential for anti-tumor effects. In some studies that have assessed immune infiltrates, only STm or E. coli that were engineered to deliver an immunestimulatory product elicited a significant immune response (19,20). Other studies have shown induction of an immune response, such as induction of IL-1b and TNF-a when delivered i.v.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one application of interest for SimCells highlighted in this study is bacterial cancer therapy (9). As it is known that some bacteria preferentially associate with tumors (10), synthetic biology tools and concepts can be used to further engineer bacteria to sense, target, and deliver anticancer compounds locally to tumors (11)(12)(13)(14). SimCells offer an additional advantage as a therapeutic agent as they cannot replicate due to the lack of chromosomal DNA.…”
mentioning
confidence: 99%